The functional diversity of the directorial vision in the political theater cinema as a model (Al-Academy, 2022)
It is very necessary for the political theater to be within the space of every theatrical performance, so that the theater carries the diverse and enlightened values and cultures of this world. political theatre. In the first chapter, the researcher dealt with (the methodological framework), which includes the research problem identified by the researcher with the following question (the functional diversity of the directorial vision in the political theater)Importance, purpose, limits and seal by defining terminology.In the second chapter, the researcher dealt with the theoretical framework on two topics, the first (transformations of directorial vision in theatrical performance) and the second topic (aesthetic experiences in political theater), in addition to the indicators that resulted from the theoretical framework.As for the third chapter, it contained (research procedures) that included the research community and the research sample represented by the play (Cinema) directed by (Kazim Al-Nassar), which was analyzed starting from the text on which the events were built and ending with the last detail in the theatrical presentation and its tools and the descriptive analysis method and the analysis of the research sample in the intentional way. While the fourth chapter included the results of the research and their discussion according to the analysis of the sample